The renaissance soul : how to make your passions your life : a creative and practical guide - Lobenstine, Margaret, ....- (New York : The Experiment, 2013)
The guide to leading a creative, passionate, and multifaceted life―big enough to embrace all your dreams Are you unwilling to settle on doing just one thing “for the rest of your life”? Do you jump at the chance to learn something new―or, after achieving success in one field, find yourself yearning for new challenges and looking around for something different to do? If so, you may be a Renaissance Soul. The Renaissance Soul is the first book devoted to this personality type, and in this updated edition―in paperback for the first time― author Margaret Lobenstine offers a life-planning strategy perfectly in tune with those who fear becoming “a jack-of-all-trades and master of none.” Discover how to design a vibrant, fulfilling life and how to: • Manage your time the Renaissance Soul way • Thrive on many interests without feeling scattered or overwhelmed • Pursue your passions even if they “don't pay” • Carry your dreams forward no matter what your day job is. Stocked with creative, doable exercises, relevant resources, and interviews with successful Renaissance Souls, this is “one self-help book that is exactly as advertised, well thought out and offering sage advice” (Boston Globe).
Keywords: Levenskunst